COMPARISON OF ANALGESIC EFFICACY OF SYSTEMIC LIGNOCAINE COMBINED WITH DEXAMETHASONE AND LIGNOCAINE INFUSION: Analgesic Efficacy in Advance Cancer Patients - Waseem, Syed Majid; Iqbal, Amjad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the analgesic efficacy of lignocaine combined with dexamethasone and lignocaine infusion in patients with advance cancer disease. Study Design: Randomized controlled trial. Place and Duration of Study: Pain centre Combined Military Hospital Rawalpindi, from Apr 2016 to Nov 2016. Material and Methods: Total 122 patients, 61 in each group, fulfilling the inclusion criteria were included in this study after approval of the ethical committee. The technique used was non probability consecutive sampling. Two groups were made; group-A received Lignocaine 2mg/kg and group-B Lignocaine 2mg/kg with dexamethasone 0.15mg/kg in continuous infusion over 30 minutes. Both regimen were administered twice weekly for a period of 12 weeks as an outdoor procedure. Numerical rating scale used to measure severity of pain. Baseline and outcome parameters of all patients’ i.e. severity of persistent and breakthrough pain and percentage relief of pain were recorded and compared at 12 weeks. Mean ± standard deviations were calculated for quantitative variables, while qualitative variables presented in frequency and percentages. Chi-square test used for qualitative variables while Independent sample t-test used to compare means. A p-value <0.05 was considered statistically significant. Results: When results of group-B compared with group-A, there was a significant reduction in severity of persistent pain from 5.68 ± 2.08 to 2.83 ± 1.01 (p-value <0.05), breakthrough pain from 5.90 ± 2.07 to 3.06 ± 1.09 (p-value <0.05). The percentage relief of pain was 45.08 ± 15.01 (%) when compared to baseline i.e. 23.35 ± 8.55 (%) (p-value <0.05). Conclusion: Lignocaine with dexamethasone has shown to be effective in reducing complex cancer related pain and disability when compared with Lignocaine alone.